Disposition to critical thinking, anxiety due to COVID-19 and academic self-efficacy in university students - Abanto-Ramirez, Carlos D.; Turpo-Chaparro, Josué E.; Apaza, Abel; López-Gonzales, Javier Linkolk (Frontiers in Education, 2024)
Introduction The present study aims to determine whether anxiety due to COVID-19 (AC) and disposition to critical thinking (DCT) predict academic self-efficacy (AS). Method The study is non-experimental, predictive, and cross-sectional. The sample was made up of 218 university students from northern Peru. The instruments used were the CAS, CTDS, and the EAPESA. Results The results showed that the AS was negatively and positively related to AC and DCT, respectively. AS in university students was significantly predicted by DCT (p < 0.01), while AC was not a significant predictor (p > 0.05). Conclusion DCT is a significant predictor of AS, while AC ins not. Strategies must be sought to improve and support this important aspect in each student to improve their disposition to critical thinking and academic self-efficacy. It is recommended for future studies to continue investigating variables associated with academic factors, such as those in this study, that lead to taking action for the effective development of university students.